Views on unwanted effects of leave-on emollients and experiences surrounding their incidence - Oakley, Robert; Lawton, Sandra (British Dermatological Nursing Group, 2016)
Background: The mainstay treatment for eczema is leave-on emollients. The aim of this study was to find out more about unwanted effects that have been reported with their use, as little is known due to a lack of formal reporting.